2001
DOI: 10.1074/jbc.m103588200
|View full text |Cite
|
Sign up to set email alerts
|

Recombinational and Mutagenic Repair of Psoralen Interstrand Cross-links in Saccharomyces cerevisiae

Abstract: Psoralen photoreacts with DNA to form interstrand cross-links, which can be repaired by both nonmutagenic nucleotide excision repair and recombinational repair pathways and by mutagenic pathways. In the yeast Saccharomyces cerevisiae, psoralen cross-links are processed by nucleotide excision repair to form double-strand breaks (DSBs). In yeast, DSBs are repaired primarily by homologous recombination, predicting that cross-link and DSB repair should induce similar recombination end points. We compared psoralen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Physical analysis confirmed that the difference was due to the direction of gene conversion. In previous studies in repair-proficient cells (30) we observed a bias in the directionality of damage-induced gene conversion within HIS3. DSBs placed in the middle of the HIS3 gene induced more conversion in the 3Ј (downstream) direction than in the 5Ј (upstream) direction.…”
Section: Table V Psoralen Cross-link-induced Mutationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Physical analysis confirmed that the difference was due to the direction of gene conversion. In previous studies in repair-proficient cells (30) we observed a bias in the directionality of damage-induced gene conversion within HIS3. DSBs placed in the middle of the HIS3 gene induced more conversion in the 3Ј (downstream) direction than in the 5Ј (upstream) direction.…”
Section: Table V Psoralen Cross-link-induced Mutationsmentioning
confidence: 99%
“…Homologous Recombination-deficient Strains-HR is the major repair pathway for DSB repair in S. cerevisiae (11), and the induction of recombination by interstrand cross-links is thought to be due to DSB-containing intermediates in crosslink repair (1,6,7,30). We examined repair, recombination, and mutation in strains deficient in the HR genes RAD51, RAD52, RAD54, RAD55, and RAD57.…”
Section: Alternate Pathways Of Cross-link Repairmentioning
confidence: 99%
See 3 more Smart Citations